A Simulated Novel Approach for Identifying Black Hole Attack in AODV based MANET - Lakhani, Kanika (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2005)
Security is an essential requirement in mobile ad hoc networks to provide protected communication between mobile nodes. Due to unique characteristics of MANETS, it creates a number of consequential challenges to its security design. To overcome the challenges, there is a need to build a powerful, multifeatured security solution that achieves both broad protection and desirable network performance. MANETs are vulnerable to various attacks, blackhole, is one of the possible attacks. Black hole is a type of routing attack where a malicious node advertise itself as having the shortest path to all nodes in the environment by sending fake route reply. By doing this, the malicious node can deprive the traffic from the source node and can be implemented as a denial-of-service attack where the packets can be dropped later on. In this paper, a solution is proposed to identify the malicious node and implanting security against the threats of blackhole by notifying other nodes in the network of the incident. The simulation of the proposed algorithm demonstrates that the solution prevents the nodes in the network from blackhole attack and also improves the overall performance of AODV in the presence of black hole attack.